From Constantinople to the Frontier
1 online resource (xxiv, 520 pages)
Keywords: From Constantinople to the Frontier: The City and the Cities provides twenty-five articles addressing the concept of centres and peripheries in the late antique and Byzantine worlds, focusing specifically on urban aspects of this paradigm. Spanning from the fourth to thirteenth centuries, and ranging from the later Roman empires to the early Caliphate and medieval New Rome, the chapters reveal the range of factors involved in the dialectic between City, cities, and frontier. Including contributions on political, social, literary, and artistic history, and covering geographical areas throughout the central and eastern Mediterranean, this volume provides a kaleidoscopic view of how human actions and relationships worked with, within, and between urban spaces and the periphery, and how these spaces and relationships were themselves ideologically constructed and understood. Contributors are Walter F. Beers, Lorenzo M. Bondioli, Christopher Bonura, Lynton Boshoff, Averil Cameron, Jeremiah Coogan, Robson Della Torre, Pavla Drapelova, Nicholas Evans, David Gyllenhaal, Franka Horvat, Theofili Kampianaki, Maximilian Lau, Valeria Flavia Lovato, Byron MacDougall, Nicholas S.M. Matheou, Daniel Neary, Jonas Nilsson, Cecilia Palombo, Maria Alessia Rossi, Roman Shliakhtin, Sarah C. Simmons, Andrew M. Small, Jakub Sypiański, Vincent Tremblay and Philipp Winterhager.